Review of Lepidocyrtinus Börner, 1903 (Collembola, Entomobryidae, Seirinae): the African species - Cipola, Nikolas Gioia; de Morais, José Wellington; Bellini, Bruno Cavalcante (Zootaxa, 2020)
Herein Lepidocyrtinus Börner is reviewed based on African species and a new diagnosis to the genus is provided, including the description of intermediary stages of two species and a proposal for the interpretation of the dorsal chaetotaxy based in juveniles. In total, 17 species previously assigned as Seira Lubbock are transferred to Lepidocyrtinus, and three of them are redescribed: L. barnardi Womersley and L. dayi Yosii from South Africa, and L. voeltzkowi (Börner) from Madagascar. Neotypes are designated for these last two species. In addition, nine new species are described from Africa: one from Botswana, two from Republic of the Congo, two from South Africa, and four from Madagascar. Finally, identification keys for the current genera of Seirinae and for the African species of Lepidocyrtinus are provided. After our revision, Lepidocyrtinus has now its generic status revalidated with 36 species, 29 of them from African continent, two from Oceania and five from Brazil.